1923 Conn. Acts 3707, An Act Concerning the Possession Sale and Use of Pistols and Revolvers, ch. 252, §2 - (:unkn) unknown (General Publisher, 1923)
Prohibited advertising, selling, delivering, offering or exposing for sale, possessing within intent to sell any pistol or revolver at retail without a permit.
--
Keywords: TRANSFER